Experimental investigations of potassium chemistry in premixed flames. (1st September 2017) - Leffler, Tomas; Brackmann, Christian; Weng, Wubin; Gao, Qiang; Aldén, Marcus; Li, Zhongshan
Graphical abstract: Highlights: Optical measurements of alkali species in premixed laminar flames seeded with KCl. Quantitative species concentrations have been evaluated from experimental data. Measurements show good agreement with predictions of a chemical mechanism. Abstract: Quantitative potassium species concentrations have been measured in alkali-seeded premixed methane-air flames of different stoichiometry. Potassium chloride (KCl) and hydroxide (KOH) were measured by broadband UV absorption spectroscopy and laser-induced photofragmentation fluorescence, while atomic potassium was measured using tuneable diode-laser spectroscopy. In addition, laser Rayleigh scattering was employed for temperature measurements. Investigations were made for different alkali-seeding levels and chlorine loads resulting in KCl/KOH concentrations up to ∼30 ppm and concentrations of K atoms at ppm levels. Experimental results were compared with predictions from a chemical mechanism used in a homogenous reactor model. The observed trends, decrease in KCl and KOH concentrations and increase in K-atom concentrations with flame equivalence ratio, were well reproduced in simulations and are compared with results reported in literature. In addition, possibilities using the experimental methods for further investigations of alkali-related combustion phenomena and detailed model validation of alkali chemistry are discussed.